Analysis of grade of service (GoS) in mobile communication using GoS calculator: article / Mohd Danial Rozaini - Rozaini, Mohd Danial (2014)
This paper proposes a Grade of Service (GoS) calculator created using Matlab software in order to calculate the probability of a call being blocked or delayed. The aim of this project is to analyze the data that we get from the calculator by using three different formulas. The calculator used Erlang B formula to obtain the value of GoS and to get more accurate value; extended Erlang B formula can be applied. From the calculated values, comparison between Erlang B and extended Erlang B can be made. The probability that a call is queued and the average call waiting time, a.k.a. the Average Speed of Answer (ASA) can be measured using Erlang C formula. The various values obtained from Erlang C calculator can tell how long subscribers need to wait before they can make a call during peak hours.